(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
The present investigation consists of promoting the community Integration of the Agricultural Technical Schools, for the promotion of socio-productive projects for the contribution to the economic development of Venezuela, the investigation belongs to the qualitative paradigm, it is based on the phenomenological-hermeneutical method. The technique used was the semi-structured interview, the instruments used were the interview guide and the field diary. For this, a model is proposed that allows the promotion of school community integration, promoting citizen participation, function of improving the quality of educational processes, that teachers, students, workers and administrative staff, parents and representatives work as a team in accordance with the policies Venezuelan educational so that as a team they can solve their community problems by promoting socio-productive and academic projects.